Climate-driven changes in forest succession and the influence of management on forest carbon dynamics in the Puget Lowlands of Washington State, USA - Laflower, Danelle M.; Hurteau, Matthew D.; Koch, George W.; North, Malcolm P.; Hungate, Bruce A. (Forest ecology and management, 2016)
•We simulated the effects of projected climate and management on forest carbon.•Climate under high emissions caused a decline in the size of the carbon sink.•Thinning and burning treatments increased the carbon sequestration rate.•Treatment effects on productivity did not compensate for changing climate.•The high emissions response was driven by species-specific responses. Projecting the response of forests to changing climate requires understanding how biotic and abiotic controls on tree growth will change over time. As temperature and interannual precipitation variability increase, the overall forest response is likely to be influenced by species-specific responses to changing climate. Management actions that alter composition and density may help buffer forests against the effects of changing climate, but may require tradeoffs in ecosystem services. We sought to quantify how projected changes in climate and different management regimes would alter the composition and productivity of Puget Lowland forests in Washington State, USA. We modeled forest responses to four treatments (control, burn-only, thin-only, thin-and-burn) under five different climate scenarios: baseline climate (historical) and projections from two climate models (CCSM4 and CNRM-CM5), driven by moderate (RCP 4.5) and high (RCP 8.5) emission scenarios. We also simulated the effects of intensive management to restore Oregon white oak woodlands (Quercus garryana) for the western gray squirrel (Sciurus griseus) and quantified the effects of these treatments on the probability of oak occurrence and carbon sequestration. At the landscape scale we found little difference in carbon dynamics between baseline and moderate emission scenarios. However, by late-century under the high emission scenario, climate change reduced forest productivity and decreased species richness across a large proportion of the study area. Regardless of the climate scenario, we found that thinning and burning treatments increased the carbon sequestration rate because of decreased resource competition. However, increased productivity with management was not sufficient to prevent an overall decline in productivity under the high emission scenario. We also found that intensive oak restoration treatments were effective at increasing the probability of oak presence and that the limited extent of the treatments resulted in small declines in total ecosystem carbon across the landscape as compared to the thin-and-burn treatment. Our research suggests that carbon dynamics in this system under the moderate emission scenario may be fairly consistent with the carbon dynamics under historical climate, but that the high emission scenario may alter the successional trajectory of these forests.